2016
DOI: 10.1186/s13046-016-0410-3
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of ATM germline variants by the p53 mitotic centrosomal localization test in BRCA1/2-negative patients with early-onset breast cancer

Abstract: BackgroundVariant ATM heterozygotes have an increased risk of developing cancer, cardiovascular diseases, and diabetes. Costs and time of sequencing and ATM variant complexity make large-scale, general population screenings not cost-effective yet. Recently, we developed a straightforward, rapid, and inexpensive test based on p53 mitotic centrosomal localization (p53-MCL) in peripheral blood mononuclear cells (PBMCs) that diagnoses mutant ATM zygosity and recognizes tumor-associated ATM polymorphisms.MethodsFre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Interestingly, we observed no LOH for ATM variants, in line with the hypothesis that one mutant ATM allele may be sufficient to promote tumor initiation . Importantly, both ATM mutations were also picked up by the p53 mitotic centrosomal localization test, indicating they are functionally impaired in governing p53 centrosomal localization . Overall, our data strongly support the role of these ATM mutations in cancer development, in these families.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, we observed no LOH for ATM variants, in line with the hypothesis that one mutant ATM allele may be sufficient to promote tumor initiation . Importantly, both ATM mutations were also picked up by the p53 mitotic centrosomal localization test, indicating they are functionally impaired in governing p53 centrosomal localization . Overall, our data strongly support the role of these ATM mutations in cancer development, in these families.…”
Section: Discussionsupporting
confidence: 85%
“…This was first demonstrated in a large group of A-T patients together with their parents, as obligate healthy carriers of pathogenic mutations, compared with wild-type healthy donors [81]. A preliminary study performed on BC patients carrying germline ATM missense variants or small deletions in both exonic and intronic regions showed that p53-MCL was impaired, highlighting its potentiality for the detection of ATM pathogenic mutations also in BC [84]. These data suggest that the p53-MCL test could represent a new functional tool to easily help in the classification of ATM VUS in neoplastic diseases.…”
Section: Atm Variants and A New Possible Functional Assay: The P53 MImentioning
confidence: 96%
“…This ATM-dependent centrosomal localization of p53 is so consistent during the cell cycle as to allow us to develop a functional test to identify individuals carrying mutations in the ATM gene 29 . In particular, by measuring the percentage of mitotic cells in which p53 colocalizes with the centrosomes in lymphoblastoid cell lines (LCLs) and in cell cycle-reactivated peripheral blood mononuclear cells (PBMCs), we have been able to discriminate healthy individuals (i.e., wild-type ATM alleles; p53-MCL > 75%) from Ataxia-Telangiectasia (A-T) patients (i.e., biallelic ATM mutations; p53-MCL < 30%) and from A-T healthy carriers (i.e., monoallelic ATM mutations; p53-MCL > 40% < 60%) 29,32 . However, which is the function of the ATM-p53 axis at the centrosome is still unclear.…”
Section: Introductionmentioning
confidence: 99%